Pengaruh Latihan Alternate Leg Bound Terhadap Daya Ledak Otot Tungkai Pemain Basket - Murtiyanto, Rachmat Bakti; , Isnaini Herawati, S.Fis.,Ftr.,M.Sc; , Yulisna Mutia Sari, SSt.FT, M.Sc (GRS) (2015)
Background: Basketball is a game that the movement was complex. It has basic techniques as jump shoot , rebounds , jump ball at the beginning of the game , lay up shoot , and block really need a good explosive power of leg muscles. One of the way to increase the explosive power of leg muscles is exercise of plyometric. The exercise of plyometric is exercise with high intensity and in a short time be able to produce a strong explosive power. One of the exercise of plyometric is alternate leg bound. Objective: To know the effect of the alternate leg bound exercise to the explosive power of leg muscles basketball players. Benefits Of Research: be able to know the effect of the e of alternate leg bound exercis to the explosive power of leg muscles basketball players. Methods: This study used a quasi experimental design with pre-test and post-test Control Group Design. The sampling technique is purposive sampling with inclusion and exclusion criteria. Explosive power of leg muscles measurement in this study is to vertical jump. Analysis of the data in this study using a non-parametric test by Wilcoxon test. The Result: Statistical analysis showed a P value of 0.0001, with a significant level of P <0.05, which means there is the effect of the alternate leg bound exercise to the explosive power of leg muscles. Conclusion: There is the effect of the alternate leg bound exercise to the explosive power of leg muscles basketball players. Keywords: Plyometric, Alternate Leg Bound, Power, Explosive Power of Leg Muscles.